Global Trade and Visual Arts in Federal New England - Johnston, Patricia (Book collections on Project MUSE., 2014)
A highly original and much-needed collection that explores the impact of Asian and Indian Ocean trade on the art and aesthetic sensibilities of New England port towns in the late eighteenth and early nineteenth centuries. This diverse, interdisciplinary volume adds to our understanding of visual representations of economic and cultural changes in New England as the region emerged as a global trading center, entering the highly prized East Indies trades. Examining a wide variety of commodities and forms including ceramics, textiles, engravings, paintings, architecture, and gardens, the contribu.